2006
DOI: 10.3727/000000006783981440
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the BD Oxygen Biosensor System to Assess Isolated Human Islets of Langerhans: Oxygen Consumption as a Potential Measure of Islet Potency

Abstract: The measurement of cellular oxygen consumption rate (OCR) is a potential tool for the assessment of metabolic potency of isolated islets of Langerhans prior to clinical transplantation. We used a commercially available 96-well plate fluoroprobe, the BD Oxygen Biosensor System (OBS), to estimate OCR in 27 human islet preparations, and compared these results to those of concurrent mouse transplantations. OCR was estimated both from the dO2 at steady state and from the transient rate of change of dO2 during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…The majority of the methods currently being used to assess islets are expensive or cumbersome and the data are difficult to reproduce. [23][24][25][26][27][28] The current standard method to assess islet quality is to transplant islets into diabetic immunodeficient rodents. 29,30 However, the results are typically not available until long after islets are transplanted into a patient, given the time required to reverse diabetes in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the methods currently being used to assess islets are expensive or cumbersome and the data are difficult to reproduce. [23][24][25][26][27][28] The current standard method to assess islet quality is to transplant islets into diabetic immunodeficient rodents. 29,30 However, the results are typically not available until long after islets are transplanted into a patient, given the time required to reverse diabetes in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare study, we showed that this method for determining the estimate of the islet in the high-glucose Krebs buffer divided by the DNA content-normalized OCR estimate β-cell viability index predicted posttransplant outcome (15). Briefly, 1,000 islet equivalents (IEQ) of porcine of the islet in the low-glucose Krebs buffer (8). islets were dispersed into single-cell suspensions in 1 ml Assessment of Islet Function In Vivo accutase solution (Innovative Cell Technologies, Inc., San Diego, CA, USA) for each stain.…”
Section: Porcine Pancreas Procurement and Islet Isolationmentioning
confidence: 99%
“…Oxygen consumption rate assessment: Cellular oxygen consumption as a marker of islet potency was performed as previously described (25). Briefly, triplicate aliquots of 500 IEQ, in low (2.2 mM) and high (22 mM) glucose Krebs buffer solution, respectively, were placed in a commercially available plate-based oxygen biosensor.…”
Section: Islet Cell Viabilitymentioning
confidence: 99%